EPIDEMIOLOGICAL CHARACTERISTICS AND PATTERNS OF PELVIC FRACTURES AT HOC MON REGIONAL GENERAL HOSPITAL FROM JANUARY 2023 TO JUNE 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the epidemiological characteristics and injury patterns of pelvic fractures, and to discuss the need for surgical intervention in unstable pelvic fractures at Hoc Mon regional General Hospital from January 2023 to June 2025.Subjects and methods: A retrospective cross-sectional descriptive study. Pelvic fractures were classified according to the Tile and Young-Burgess classification systems. Data collected included age, sex, mechanism of injury, fracture pattern, degree of pelvic instability, and initial management.Results: During the study period, 96 cases of pelvic fracture were recorded, of which 65.6% were female and 34.4% were male. Patients aged over 60 years accounted for the largest proportion (52.1%). The most common injury pattern was sacroiliac fracture-dislocation (35.4%), followed by pubic fractures (29.1%) and iliac or pelvic body fractures (20.8%). According to the Young-Burgess classification, lateral compression injuries were the most frequent mechanism. The number of pelvic fracture cases increased annually, from 19 cases in 2023 to 49 cases in 2024, with 28 cases recorded in the first half of 2025. All patients were transferred to higher-level hospitals for definitive management or discharged at their own request.Conclusion: Pelvic fractures predominantly affected middle-aged and elderly women and showed an increasing trend over the study period. The majority of cases involved unstable injury patterns requiring specialized management. Because the study data only reflects patients who initially visited the regional hospital, the actual incidence of pelvic fractures in the Hoc Mon area may be higher. These findings highlight the importance of strengthening diagnostic capacity, initial management, and surgical training for pelvic fracture care at district general hospitals.
Keywords: Pelvic fracture, sacroiliac dislocation, pelvic injury, acetabular fracture.